Analysis of electromechanical systems based on the absolute nodal coordinate formulation - Nemov, Alexander S.; Matikainen, Marko K.; Wang, Tengfei; Mikkola, Aki (Acta mechanica, 2022)
The absolute nodal coordinate formulation (ANCF) approach has been successfully used to analyze bodies undergoing large deformations in multibody dynamics applications. In this study, the ANCF is extended to the analysis of coupled electromechanical systems. To this end, the electrostatic equations are solved by means of conventional plane finite elements, and the ANCF is used to describe the geometrically nonlinear elastic deformation of a thin beam. Bidirectional coupling between electrostatic and elastic domains was introduced using an iterative staggering algorithm. The results illustrate that the ANCF approach can be applied to electromechanical problems when objects are discretized using beam and plate elements. Two numerical examples of microbeams subject to an electrostatic field are used to validate the proposed solution strategy and to reveal characteristic features of fully coupled electromechanical solutions accounting for finite strain theory.